MOTIVATIONAL FACTORS FOR THE FORMATION OF KEY SIDES OF COOPERATION BETWEEN NATIONAL OR REGIONAL AUTHORITIES AND ENTREPRENEURAL STRUCTURES - Denis A. Faleev; Sergey A Lapshinov (Статистика и экономика)
Article retrctedThe main aspects of cooperation in the economic system of the region are concretized. It is shown that the parties of cooperation have their own interests, due to the goals and tasks of functioning. Core interests of the various parties on the basis of which has developed a system of incentives for the establishment of a multilateral cooperation between authorities with business structures are isolated and grounded.